PENGEMBANGAN PEMBELAJARAN PAI-BAHASA ARAB PADA ASPEK PSIKOMOTORIK (KETERAMPILAN) DI MI AL-IBROHIMI-SIDOARJO - Wiwin Nur Istiqomah; Syafi’i Syafi’i (Program Studi Pendidikan Bahasa Arab Unisda Lamongan, 2021)
In learning PAI-Arabic psychomotor development will produce an action in the form of skills. So that it makes students who have character in the teaching and learning process at school. Examples in Islamic religious education are fiqh material, namely practicing the ablution movement correctly, demonstrating the prayer movement correctly and so on. Whereas in Arabic, students can converse with their friends using correct and fluent Arabic. This research uses descriptive analytic method. Where the researchers started with a survey technique with the aim of obtaining an empirical description of the learning outcomes of Islamic. Religious education and Arabic as a basis for supporting psychomotor aspects (skills) in PAI-BA learning therefore, researchers area interested in taking the title development of islamic relig PAI-Arabic Learning, Therefore, researchers are interested in taking the title development of Islamic relig PAI-Arabic Learning, Psychomotor Aspects (Skills) ious Education Learning and Arabic in Psychomotor Aspects (Skills) at MI AL-Ibrohimi – Sidoarjo.